USING UNINTERRUPTED SUSTAINED SILENT READING (USSR) STRATEGY IN TEACHING READING COMPREHENSION TO SENIOR HIGH SCHOOL STUDENTS - Reza Asmaniarti; Ratmanida Ratmanida (Universitas Negeri Padang, 2018)
Reading is an important skill that is needed in order to get information from written text. In reading, the students not only must be able to read the text, but they also must be able to comprehend the text in order to get the meaning from the text. However, many students have difficulties in comprehending the text and lacking motivation in reading. It is because there is a tendency that the teachers do not use an interesting strategy that can attract students’ interest. That is why this paper is conducted in order to explain how to use Uninterrupted Sustained Silent Reading (USSR) strategy in teaching reading comprehension to senior high school students. USSR strategy is conducted by providing the students to select their own reading material based on their interest and read it silently about twenty minutes without any interruption. This strategy can make the students relaxed and enjoyed the reading process. It is believed that this strategy can help many students in improving their reading comprehension ability. Key words: Reading, Reading Comprehension, USSR strategy